Neighbourhood residential density and childhood obesity - Zou, Yuxuan (Obes Rev, 2020)
Residential density is considered an important attribute of the built environment that may be relevant to childhood obesity. However, findings remain inconclusive, and there are no reviews yet on the association between residential density and childhood obesity. This study aimed to systematically review the associations between residential density and weight‐related behaviours and outcomes. A comprehensive literature search was conducted using the Cochrane Library, PubMed and Web of Science for articles published before 1 January 2019. A total of 35 studies conducted in 14 countries were identified, including 33 cross‐sectional studies, one longitudinal study and one containing both study designs. Residential density was measured by Geographic Information Systems in 28 studies within a varied radius from 0.25 to 2 km around the individual residence. Our study found a general positive association between residential density and physical activity (PA); no significant associations were observed. This study provided evidence for a supportive role of residential density in promoting PA among children. However, it remained difficult to draw a conclusion between residential density and childhood obesity. Future longitudinal studies are warranted to confirm this association.